MODAL MINIMALIS MEMBAWA BERKAH DI MASA PANDEMI COVID-19: PELATIHAN DARING OJEK ONLINE - Wijirahayu, Suciana (Jurnal Abdimas Adpi Sosial dan Humaniora, 2020)
This public service is inspired by the previous action as one of the volunteers in UHAMKA Covid- 19 action. There were 100 Engineering students’ Online motorbike drivers involved in the project yet the recovery of the pandemi is not over. Therefore further programs in the form of creative industry is provided to develop literacy in enterpreneuship. Practitioners are invited in online workshop to support and inspire the participants who are the drivers and the teachers from vocational high school.